A Journey in Other Worlds: A Romance of the Future - Astor, John Jacob, 1864-1912 (Salt Lake City, UT : Project Gutenberg, 1999)
"A Journey in Other Worlds: A Romance of the Future" by John Jacob Astor is a science fiction novel published in 1894. Set in the year 2000, it envisions a world transformed by technological marvels: worldwide telephone networks, solar power, and space travel. American explorers journey to Jupiter, encountering a dangerous jungle world filled with monstrous creatures and vast resources. On Saturn, they meet ancient spirits who reveal troubling prophecies about their fates and describe Cassandra, a distant icy world harboring unworthy souls. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/A_Journey_in_Other_Worlds
Release date is 1999-01-01
HTML version by Dave Skalick.
Keywords: Science fiction; Utopias -- Fiction; Space ships -- Fiction; Manned space flight -- Fiction; Jupiter (Planet) -- Fiction; Saturn (Planet) -- Fiction